Investigation of VTP:PC71BM organic composite as highly responsive organic photodetector - Roslan, Nur Adilah; Abdullah, Shahino Mah; Abd Majid, Wan Haliza; Supangat, Azzuliani (Elsevier, 2018)
In this work, we report the use of vanadyl 3,10,17,24-tetra-tert-butyl-1,8,15,22-tetrakis(dimethylamino)-29H,31H-phthalocyanine (VTP) in the fabrication of organic photodetector that aimed to be more responsive in the lower region of visible light. The thin active layer of the photodetector has been developed from the vanadyl 3,10,17,24-tetra-tert-butyl-1,8,15,22-tetrakis(dimethylamino)-29H,31H-phthalocyanine (VTP) [6,6]:-phenyl C71 butyric acid methyl ester (PC71BM) blend solution. The combination of VTP and PC71BM has significantly enhanced the absorption of visible light especially below 650 nm for the ITO/PEDOT:PSS/VTP:PC71BM/Al photodetector. The detector showed good photocurrent-illumination linearity, fast response-recovery time and high consistency towards the rapid change of light intensities. It is found that the detector exhibits a good photoresponsivity of 2.30 × 10-1 A/W.